2021
DOI: 10.48550/arxiv.2109.07545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The MUSE Extremely Deep Field: Evidence for SFR-induced cores in dark-matter dominated galaxies at z=1

Nicolas F. Bouché,
Samuel Bera,
Davor Krajnovic
et al.

Abstract: Context. Disc-halo decompositions z = 1 − 2 star-forming galaxies (SFGs) at z > 1 are often limited to massive galaxies (M > 10 10 M ) and rely on either deep Integral Field Spectroscopy data or stacking analyses. Aims. We present a study of the dark-matter (DM) content of 9 z ≈ 1 SFGs selected among the brightest [O ii] emitters in the deepest Multi-Unit Spectrograph Explorer (MUSE) field to date, namely the 140hr MUSE Extremely Deep Field. These SFGs have low stellar masses, ranging from 10 8.5 to 10 10.5 M … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 162 publications
0
6
0
Order By: Relevance
“…Some authors also implement an asymmetric drift correction to take into account the impact of gas pressure on its dynamics (e.g. Meurer et al 1996;Übler et al 2017;Abril-Melgarejo et al 2021;Bouché et al 2021). Evaluated at R 22 , the gas pressured corrected circular velocity for a double exponential density profile with a constant thickness writes (Meurer et al 1996;Bouché et al 2021)…”
Section: Impact Of the Environment On The Tfrmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors also implement an asymmetric drift correction to take into account the impact of gas pressure on its dynamics (e.g. Meurer et al 1996;Übler et al 2017;Abril-Melgarejo et al 2021;Bouché et al 2021). Evaluated at R 22 , the gas pressured corrected circular velocity for a double exponential density profile with a constant thickness writes (Meurer et al 1996;Bouché et al 2021)…”
Section: Impact Of the Environment On The Tfrmentioning
confidence: 99%
“…Meurer et al 1996;Übler et al 2017;Abril-Melgarejo et al 2021;Bouché et al 2021). Evaluated at R 22 , the gas pressured corrected circular velocity for a double exponential density profile with a constant thickness writes (Meurer et al 1996;Bouché et al 2021)…”
Section: Impact Of the Environment On The Tfrmentioning
confidence: 99%
“…Indeed, there seems to be mounting observational evidence for this scenario (e.g. Bouché et al 2021;Sharma et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A potential solution to resolve the mismatch between the ΛCDM prediction and observations is the dynamical heating caused by the potential fluctuation of the galactic gas driven by supernova feedback and radiative cooling (e.g., Pontzen & Governato 2012;Ogiya & Mori 2014;Read et al 2016). Observations showed that star formation induced cores can be formed in the centre of galaxies at 𝑧 ∼ 1 (Bouché et al 2021). However, supernova feedback would not be powerful enough to expel the gas from the centre of massive galaxies, and thus this process does not work to alter the central DM density structure of massive systems (Silk & Mamon 2012;Di Cintio et al 2014).…”
Section: Introductionmentioning
confidence: 99%